Sociocultural Activity Managers’ Professional Training in the Conditions of Information and Educational Environment - Lubarets, Vladislava; Litovka-Demenina, Svitlana; Nehodenko, Viktiria (Journal of Education, Technology and Computer Science, 2019)
The article deals with the relevance of transformational digitalization processes of the economy and education in Ukraine and in the world. It has been found out that the peculiarities of the information and educational environment lead to the requests for training the participants of the educational center on the usage of science-intensive educational information technologies. Designing the educational environment for the future sociocultural activity managers involves the development of technology to prepare them for the educational and scientific space organization and digitization.